ELECTROCATALYST CONTAINING TUNGSTEN OXIDE NANOPARTICLES - FAROOQ MUHAMMAD; MURAMATSU KEISUKE; SUGIMOTO WATARU (2024)
To provide an electrocatalyst containing tungsten oxide nanoparticles with high performance capable of significantly reducing the generation of hydrogen peroxide at the anode as an anode catalyst for solid polymer fuel cells.SOLUTION: The above problem was solved by using a composite catalyst in which tungsten oxide nanoparticles were mixed as a promoter for a platinum-supported carbon (Pt/C) catalyst. The tungsten oxide nanoparticles preferably have an average particle size within the range of 2 to 100 nm, and the ratio of the tungsten oxide nanoparticles to the sum of the platinum-supported carbon and the tungsten oxide nanoparticles is preferably within the range of 2% by weight to 10% by mass.SELECTED DRAWING: Figure 4 【課題】固体高分子形燃料電池のアノード触媒として、アノードで生成される過酸化水素の発生を大幅に減少させることができる等の高い性能を示す、酸化タングステンナノ粒子を含む電極触媒を提供する。【解決手段】酸化タングステンナノ粒子を白金担持カーボン（Ｐｔ／Ｃ）触媒の助触媒として混合した複合触媒により上記課題を解決した。酸化タングステンナノ粒子は平均粒径で２～１００ｎｍの範囲内であることが好ましく、白金担持カーボンと酸化タングステンナノ粒子との和に対する酸化タングステンナノ粒子の割合が２重量％以上１０質量％の範囲内であることが好ましい。【選択図】図４